Todder Care / June Thompson ; penerjemah Novite Jonathan ; editor Dyah Novita Handayani, Theresia Vini S. - Thompson, June; Jonathan, Novita; Handayani,Dyah Novieta; Vini s, Theresia (2003)
104 hlm ilus 26 cm